Wychowanie dziewcząt w działalności i poglądach bł. Marceliny Darowskiej - Knop, Marcelina (Biuletyn Historii Wychowania, 2016)
The article presents the life and educational activities of Blessed Marcelina Darowska, the cofounder of the Convent of the Immaculate Conception of the Blessed Virgin Mary, and her views on upbringing of young women. Mother Marcelina’s perception of education of girls in the 19th century seemed modern and beyond her time. In her opinion, there was a need of putting a stop to producing “parlour dolls” and provide young women with practical education. For the betterment of the country, she set up schools in Jazłowiec, Jarosław, Niżniów and Nowy Sącz. The girls attending the schools were brought up according to the system developed by Marcelina Darowska, based on religious and patriotic values. The Convent of the Immaculate Conception of the Blessed Virgin Mary continues the work commenced by its founder; over time Mother Marcelina’s message remains valid and serves the subsequent generations of young Polish girls.